Mot en begreppsbaserad isländsk och svensk fraseologisk ordbok. Reflektioner kring pragmatiska idiom - Hannesdóttir, Anna Helga; Jónsson, Jón Hilmar; Tingsell, Sofia (Nordiske Studier i Leksikografi, 2010)
In traditional dictionaries, phrases and phrasemes are listed under one of the lexical units occurring in the phrase. Thus, phraseology in dictionaries is less accounted for in its own right. For bilingual dictionaries, this also results in phrasemes in the target language being dependant on the structure and lexicon of a corresponding phraseme in the source language. In an electronic dictionary, the lexicographer is free to structure phrasemes in a different manner. In one of the projects related to ISLEX, an electronic dictionary of Icelandic and the Scandinavian languages, the focus is on Icelandic and Swedish phraseology. In this project, Icelandic and Swedish phrasemes are listed under corresponding semantic groups. This thesauristic structure will make it possible for the user to search for equivalents in the other language to a specific meaning rather than to a specific form. Furthermore, the dictionary includes what might be described as “pragmatic idioms”, routine formulas, most often belonging to the spoken language, linked to specific speech acts. They typically lack a pregnant lexical unit, which makes them hard to deal with in traditional dictionaries. In this paper we present one possible way of accounting for such phrases in an accessible way.